Reminiscences and recollections - Ware, Kallistos (St Vladimir's Seminary Press, 2025)
People all over the world know Met. Kallistos Ware as a church leader, scholar, and writer. But far fewer know him as a man. Near the end of his life, he agreed to sit for several sessions and speak about his life (his childhood and upbringing, his schooling and scholarly career, his conversion to Orthodoxy, and his travels and experiences in church life) as well as his memories of the many different people he met and knew over the years (C. S. Lewis, J. R. R. Tolkien, Philip Sherrard, Met. Anthony Bloom, St Sophrony, and many others) and to give his thoughts on some contemporary questions facing the Church in our age. These sessions were recorded, transcribed, and edited for the present volume. Readers of "The Orthodox Church", "The Orthodox Way", and the English translation of the "Philokalia" can now learn how these publications came to light, and come to know the man behind these books in a new and deeper way. Further, some of the most prominent figures in the Orthodox world in the past century make various appearances in the life of Met. Kallistos. Those who read this book will come to appreciate not only his brilliant intellect but also his warm heart and ready wit.--Publisher
Includes bibliographical references and index
Keywords: Kallistos -- Bishop of Diokleia -- 1934-2022; Orthodox Eastern Church -- Biography; Orthodox Eastern Church -- Doctrines; Oxford (England) -- Church history -- 20th century